Recent Advances in Classical and Non-Classical Antifolates as Antitumor and Antiopportunistic Infection Agents: Part I - Gangjee, Aleem; Jain, Hiteshkumar D.; Kurup, Sonali (Anti-Cancer Agents in Medicinal Chemistry, 2007)
Antifolates that inhibit the key enzymes thymidylate synthase (TS) and dihydrofolate reductase (DHFR) have found clinical utility as antitumor and antiopportunistic agents. Methotrexate MTX, (1) and 5-fluorouracil (5-FU) were among the first clinically useful DHFR and TS inhibitors, respectively. The development of resistance to 5-FU, its occasional unpredictable activity and toxicity resulted in the search of novel antifolates. Pemetrexed (4) and raltitrexed (5) specifically inhibit TS, and are clinically useful as antitumor agents. A major mechanism of tumor resistance to clinically useful antifolates is based on their need for polyglutamylation via the enzyme folylpoly-γ-glutamate synthetase (FPGS). Novel antifolates have been developed that do not need to be polyglutamylated and include plevitrexed (6) and GW1843 (7). Nonclassical antifolates for antitumor and parasitic chemotherapy, such as nolatrexed (8), trimethoprim TMP, (11) and piritrexim PTX, (12), can passively diffuse into cells and hence do not have to depend on FPGS or the reduced folate carrier (RFC). Variations in the structures of antifolates have helped delineate the structural influence on the interaction with TS, DHFR, FPGS, and RFC utilization. The differences in the active site of human and pathogen DHFR have also been exploited. The literature contains excellent reviews on the design and synthesis of antifolates prior to 1996. This two-part review discusses the design, synthesis and structural requirements for TS and DHFR inhibition and their relevance to antitumor and parasitic chemotherapy, since 1996. Monocyclic and 6-5 fused bicyclic antifolates will be discussed in Part I, while 6-6 bicyclic and tricyclic antifolates will be discussed in Part II.
Keywords: Folate